Sound waves in polydomain ferroelectrics - Serdobolskaya, O. Yu; Morozova, G. P. (Ferroelectrics, 1998)
Some theoretical and experimental results concerning propagation, generation and interaction of sound waves in polydomain ferroelectrics (lead germanate and gadolinium molibdate) are presented. The following subjects are considered: sound reflection from a plane domain wall; second acoustic harmonic generation in polydomain ferroelastic; sound scattering on the system of cylindrical domains; sound propagation along a regular system of plane domain walls; domain-acoustic transducers and their applications; investigation of domain 'memory'by acoustic methods; acoustic emission in switching process.